2011
DOI: 10.1038/ejhg.2011.47
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional data implicate the Arg(151)Ser variant of MSX1 in familial hypodontia

Abstract: Multiple previous reports confirm that several missense alleles of MSX1 exhibit Mendelian inheritance of an oligodontia phenotype (agenesis of more than six secondary teeth besides third molars). However, the extent to which missense MSX1 alleles contribute to common, multifactorial disorders is less certain. It is still not yet clear whether multiple non-synonomous MSX1-coding variants identified among patients with oral clefting are merely neutral polymorphisms or whether any of these might represent real mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 62 publications
(75 reference statements)
0
22
0
Order By: Relevance
“…17,22,26,29 Oral clefts are more severe than tooth agenesis, and recent data suggest that MSX1 causative mutations for tooth agenesis may not be sufficient to cause oral clefts. 29 In addition, the change in amino acid itself may not be a sufficient criterion to predict disease in complex traits such as oral clefts. 24 Therefore, these rare variants could, at best, contribute to clefting as part of a complex inheritance pattern, with both additional genes and environmental factors having a role.…”
Section: Discussionmentioning
confidence: 99%
“…17,22,26,29 Oral clefts are more severe than tooth agenesis, and recent data suggest that MSX1 causative mutations for tooth agenesis may not be sufficient to cause oral clefts. 29 In addition, the change in amino acid itself may not be a sufficient criterion to predict disease in complex traits such as oral clefts. 24 Therefore, these rare variants could, at best, contribute to clefting as part of a complex inheritance pattern, with both additional genes and environmental factors having a role.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted using a DNeasy Blood and Tissue Kit (Qiagen, Valencia, CA, USA). The entire coding regions of MSX1 , PAX9 , and AXIN2 , including splice sites, were amplified using specific primers for MSX1 and PAX9 described in previous reports or specific primers for AXIN2 that were synthesized on the basis of intronic sequences obtained from GenBank (Table S1). PCR products were resolved by electrophoresis through a 1.2% agarose gel and then purified using a Fast Gene Gel/PCR Extraction Kit (Nippon Genetics, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Kamamoto et al. reported a p.R151S mutation with moderately penetrant non‐syndromic tooth agenesis . This mutation was also associated with unilateral cleft lip and palate in another single Japanese proband .…”
mentioning
confidence: 97%
“…On the other hand, MSX1 p.S104X (4) and p.S202X (16) mutations, and the deletion of the short arm of chromosome 4 (17), produce tooth agenesis associated with other symptoms. Recently, Kamamoto et al reported a p.R151S mutation with moderately penetrant non-syndromic tooth agenesis (18). This mutation was also associated with unilateral cleft lip and palate in another single Japanese proband (19).…”
mentioning
confidence: 99%